Comparative Analysis of Cuticular Wax in Various Grape Cultivars During Berry Development and After Storage - Zhang, Mengwei; Zhang, Peian; Lu, Suwen; Ou-yang, Qixia; Zhu-ge, Yaxian; Tian, Ruiping; Jia, Haifeng; Fang, Jinggui (Frontiers in Nutrition, 2021)
Cuticular wax covering the surface of fleshy fruit is closely related to fruit glossiness, development, and postharvest storage quality. However, the information about formation characteristics and molecular mechanisms of cuticular wax in grape berry is limited. In this study, crystal morphology, chemical composition, and gene expression of cuticular wax in grape berry were comprehensively investigated. Morphological analysis revealed high density of irregular lamellar crystal structures, which were correlated with the glaucous appearances of grape berry. Compositional analysis showed that the dominant wax compounds were triterpenoids, while the most diverse were alkanes. The amounts of triterpenoids declined sharply after véraison, while those of other compounds maintained nearly constant throughout the berry development. The amounts of each wax compounds varied among different cultivars and showed no correlation with berry skin colors. Moreover, the expression profiles of related genes were in accordance with the accumulation of wax compounds. Further investigation revealed the contribution of cuticular wax to the water preservation capacity during storage. These findings not only facilitate a better understanding of the characteristics of cuticular wax, but also shed light on the molecular basis of wax biosynthesis in grape.